Electric Charging and Colloid Stability of Fabricated Nedle-Like \(TiO_2\) Nanoparticles - Ueno, Kento; Kobayashi, Motoyoshi; Adachi, Yasuhisa; Kojima, Takashi (Communications in Physics, 2014)
Charging and stability of needle-like TiO\(_2\) nanoparticles were studied. Measured isoelectric point (IEP) was pH 4 and lower than that of spherical ones pH 6. Heat treatment at 400\( \)C changed the IEP from 4 to 6. The shift is probably due to shape controller (ethylenediamine). The particles aggregate around IEP and thus are charge-stabilized. Experimental hydrodynamic diameters of needle-like particles showed a reasonably good agreement with the theoretical diameter. That is, the particles can be dispersed to primary particles. 1pK Stern and standard electrokinetic models describe electrophoretic mobility of needle-like TiO\(_2\), indicating that double layer relaxation is significant for needle-like TiO\(_2\).